The algorithm of developing priorities in the supply chain - Zwolińska, Bożena; Tubis, Agnieszka A. (LogForum (Poznań, Poland), 2020)
Background: The presented research problem concerns the operational (executive) level and does not include tactical or strategic solutions. The described algorithm concerns the determination of the priority number of objects that are the equipment of any considered production system. The algorithm takes into account the states of work in the external and internal areas of the evaluated system. The analysed characteristics mainly include: values of work levels in the supply chain (to and from the enterprise) and values of system work levels within the company in the area of continuity of the processed material flow and failure levels of technological equipment. The algorithm of the object priority evaluation takes into account the existing synergy of a single element of the system with the whole system. Methods: The presented method of assessing priorities enables determination of critical elements of a complex system. The evaluation is carried out in a three-dimensional system. It takes into account machine failure, the operation of processes in the area of the analysed manufacturing system but also the levels of operation of supply systems (supply chains). The presented method of determining priorities requires adapting the assessment methodology to the individual characteristics of the test object. For this reason, the analysis includes, among others: the type of the system, its structural and functional complexity, complexity of interoperability and the size of material flow streams and their frequency. Results: The developed algorithm was verified on a selected example of a production system. Due to the complexity of the presented algorithm, the article presents results for a system that is characterized by a relatively high level of process flexibility and has a large number of technological processes. The article presents the values of indicators that were calculated for individual modules Conclusions: The presented algorithm is a general approach to the evaluation of the elementary objects of the system, while taking into account the existing synergy between the other elements of the entire system. In the next stages of the research, the authors will develop algorithms for various production systems (convergent and divergent), for different manufacturing specifications (objective and technological) and for different levels of process flexibility values.